Effects of operational mode on particle size and number emissions from a biomass gasifier cookstove. Issue 1 (2nd January 2018) - Tryner, Jessica; Volckens, John; Marchese, Anthony J.
ABSTRACT: Interest in the size distribution of particles emitted from biomass cookstoves stems from the hypothesis that exposure to ultrafine particles is more detrimental to human health than exposure to accumulation mode or other size regimes. Previous studies have reported that gasifier cookstoves emit smaller particles than other cookstove designs under steady operating conditions. In the present study, the number size distribution of particles emitted from a forced-air gasifier cookstove was measured at 1 Hz as the stove transitioned between several steady and transient operating modes. During normal operation, when the stove functioned as a top-lit updraft gasifier, the distribution was bimodal, with peaks at 10 nm and 40 nm, when a pot of water was on the stove. The distribution became unimodal with a peak at 10 nm when the pot was removed. Once the fuel bed had completely gasified and the secondary flame extinguished, the concentration of particles increased and the peak in number concentration shifted to approximately 80 nm. After refueling, when the stove operated as a conventional updraft gasifier, the peak in number concentration decreased to 10 nm. When the secondary flame extinguished a second time, the peak in number concentration increased to approximately 100 nm before decreasing to 20 nm during the char burn-out phase. These results demonstrate that changes in operational mode influence the combustion process and produce distinct changes in the size distribution and rate of particle emissions. Copyright © 2018 American Association for Aerosol Research